From hamlets to central places: integrated survey and excavation strategies for the social analysis of settlements in northern Europe, c. AD 400-1100 - Loveluck, Chistopher; Strutt, Kristian; Clogg, Philip (Aarhus University Press, 2014)
This article explores a range of archaeological approaches to the social analysis of rural settlements in northern Europe, dating predominantly from the first millennium AD, through the intensive use of superimposed archaeological survey and targeted excavation strategies. The overall aim is to show how superimposed survey techniques (geophysical, geochemical and surface collection) can be applied to landscapes to define the character of different land use zones within and beyond settlements. These, in turn, allow the targeting of specific areas for excavation and post-excavation analysis and ground penetrating radar (GPR) survey, for purposes of confirming the character of remains, chronology of occupation, and deposit modelling. The collective data from the survey, excavation and post-excavation phases of research can then be combined within a contextualised interpretation of settlement morphology, discard strategies and preservation conditions to produce holistic social analyses of lifestyles and settlement biographies through time.